Viscoplastic material models for soil: new insight into the soil-support interaction in NATM tunnel excavations - Spira, Y.; Lackner, R.; Pichler, Ch.; Mang, H.A. (Archives of Mechanics, 2005)
In this paper, the benefits gained from advanced material modeling of soil for the numerical simulation of soil-support interaction in tunneling processes according to the New Austrian Tunneling Method (NATM) are illustrated by means of plane-strain Finite Element (FE) analyses. The studies performed encompass different types of soil (cohesive and granular) and two types of support means (shotcrete lining and jet-grouted soil). As regards the latter, the early-age behavior of the cement-based components is taken into account by means of a coupled chemomechanical approach. The obtained results provide an insight into the benefits gained from the employed support means during NATM tunneling in different geological conditions, serving as the basis in the day-to-day decision process at NATM construction sites. Additionally, effects of the changing geological conditions on the soil-support interaction are illustrated.